PELAKSANAAN ADMINISTRASI PENGADAAN TANAH UNTUK KEPENTINGAN UMUM DI SUMATERA BARAT MENURUT KETENTUAN PERATURAN PERUNDANG-UNDANGAN - Gantika, Naldi; Netrivianti, Netrivianti (Ensiklopedia of Journal, 2025)
Abstract: Land acquisition for public interest is a crucial instrument to support national development. In West Sumatra Province, the administrative implementation of land acquisition faces unique challenges, as much of the land is communally owned by Minangkabau indigenous communities under the ulayat land system. This study aims to analyze the administrative process of land acquisition based on prevailing laws and regulations, identify the obstacles encountered in customary land areas, and examine efforts to harmonize state law and customary law within this context. The research employs a normative-empirical legal method with statutory, conceptual, and sociological approaches. The findings indicate that while administrative procedures follow national regulations, significant gaps remain in implementation within indigenous areas due to conflicting legal paradigms and the limited role of local regulations. Systemic harmonization is needed through the involvement of traditional institutions, strengthening of local technical regulations, and recognition of the socio-cultural values of indigenous peoples as an integral part of the public land acquisition process.Keywords: land acquisition, administration, customary law, ulayat land, West Sumatra.